Finite element analysis and crashworthiness evaluation of a multi-stage aluminium alloy 6061-T6 impact attenuator for Formula SAE - Aditia Pratama; Zainal Abadi; Delima Yanti Sari; Wanda Afnison (Journal of Engineering Researcher and Lecturer, 2026)
Formula SAE regulations require every prototype vehicle to be equipped with an impact attenuator as a passive safety system capable of absorbing a minimum frontal impact energy of 7,350 J at an impact velocity of 7 m/s for a vehicle with a mass of approximately 300 kg. This study aims to design an impact attenuator that satisfies the Formula SAE requirements to improve vehicle crashworthiness. Three design variations were analyzed using Finite Element Analysis (FEA) with LS-DYNA to evaluate energy absorption, impact force, acceleration/deceleration, and displacement. The accuracy of the numerical model was validated using previously published experimental data before analyzing the effect of thickness variation in each stage of the impact attenuator. The simulation results show that the optimum design is capable of absorbing impact energy above the minimum requirement of 7,350 J, exhibits a high Crash Force Efficiency (CFE), produces acceleration within the prescribed safety limits, and provides controlled deformation during the impact process. The results indicate that the proposed impact attenuator design satisfies the Formula SAE safety requirements and has the potential to be applied to prototype vehicles to improve safety performance during frontal collisions.